Establishment Of More Reliable Equations For Estimation Of Coalbed Methane Proximate Analysis Data - Bambang Widarsono; Kosasih Sartadiredja; Bambang A Widjayanto (Scientific Contributions Oil and Gas, 2009)
Coal bed methane (CBM) data such as ash contents, moisture contents, volatile matters, and fixed carbon – commonly obtained from log analysis - are direct input to calculation of gas accumulation in CBM reservoirs. However, recent studies on some coal samples taken from Rambutan field CBM pilot project have shown that the commonly used log analysis equations are simply inapplicable for the field’s coal samples. Calculation results tend to give far different magnitudes when compared to laboratory results. After a series of re-evaluations and re-measurements on the laboratory results it was convinced that the problem does not lie with the laboratory results but with these ‘conventional’ equations. Therefore modification efforts are spent to find better equations. Comparisons between measured data (coal samples taken from two coal seams in the field) and calculated data show that only equation for ash contents gives accurate results. The other proximate analysis output data - i.e. moisture contents, volatile matter, and fixed carbon – is at considerable odd with their corresponding calculated data. Modification upon the original empirical models is then carried out. The following modifications on the equations have produced analogous but different empirical equations to the original equations. These equations certainly work more reliably for the field’s coals, and these better results underline that future log analyses in the field have to use the modified equations